A Methodology to Assess Diagnostic Competence in Anatomical Pathology Examinations for Pathology Residents - Caridad Socorro Castro; Margarita Roméu Escobar (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Background: For years, the tools for learning assessment of physicians in specialization programs have had an empirical character, leading to problems in the quality of the process. Very often, these tools do not measure the fulfilment of proposed educational objectives and grades awarded to students do not reflect their practical achievements and professional skills. Objective: To develop a methodology to assess diagnostic competence in anatomical pathology examinations for Pathology residents. Method: Development research conducted in the University Hospital of Cienfuegos between 2008 and 2010. In addition to theoretical and empirical methods, experts' criteria were applied to validate the proposal. Results: A logical, stages-based design of a general methodology was created. A tool including indicators and standards was conformed to assess skills and knowledge while interns performe key activities of their specialty. The methodology was validated through experts' criteria. Conclusions: Teachers and tutors of this specialty are now provided with an unprecedented methodological tool. Its usefulness lies in a more objective assessment of knowledge and skills for diagnostic biopsies, cytology and autopsies. This procedures support diagnostic competence in pathological examinations, which is ultimately pathologists' key role. The present methodological design can be adapted and applied in the evaluation of interns from other specialties.